Importance of institutional accreditation in higher education in Ecuador - Enríquez Estrella, Miguel Ángel (2024)
Accreditation of higher education in Ecuador takes on a paramount significance for the development of academic activities. This study focuses on the distinction between evaluation and accreditation, emphasizing their relationship. The accreditation in Ecuadorian higher education is addressed, considering parameters such as teaching, research, and engagement with society, highlighting its relevance. The employed method centers on the construction and analysis of the Referential Framework, playing a crucial role in providing a clear and accessible understanding of the research topic. The results underscore the importance of continuous training and knowledge updates in university education, especially in an environment characterized by constant changes. In conclusion, the need for implementing continuous evaluation processes at all levels of the educational institution is emphasized.